2020
DOI: 10.3390/ijerph17217808
|View full text |Cite
|
Sign up to set email alerts
|

The Spanish Family Quality of Life Scales under and over 18 Years Old: Psychometric Properties and Families’ Perceptions

Abstract: Background: Family quality of life (FQoL), just like individual quality of life, has become a priority outcome in the policies and services received by persons with intellectual and developmental disabilities (IDD) and their families. Conceptualizing, measuring, and theorizing FQoL has been the object of investigation in recent decades. The goal of this paper is to present a revision of the Spanish Family Quality of Life Scales, the CdVF-E < 18 and the CdVF-E >18, and describe the FQoL of Spanish familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
8
0
1
Order By: Relevance
“…The results support the use of a multidimensional scale. This support the findings of previous studies related the scale factors ( Park et al, 2003 ; Verdugo et al, 2005 ; Balcells-Balcells et al, 2011 , 2020 ; Isaacs et al, 2012 ; Meral et al, 2013 ; Parpa et al, 2016 ; Chiu et al, 2017 ; García-Grau et al, 2018 ; Huang et al, 2018 ; Waschl et al, 2019 ; Alnahdi et al, 2021 ). The results indicated that each of the five subscales had a unidimensional scale.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results support the use of a multidimensional scale. This support the findings of previous studies related the scale factors ( Park et al, 2003 ; Verdugo et al, 2005 ; Balcells-Balcells et al, 2011 , 2020 ; Isaacs et al, 2012 ; Meral et al, 2013 ; Parpa et al, 2016 ; Chiu et al, 2017 ; García-Grau et al, 2018 ; Huang et al, 2018 ; Waschl et al, 2019 ; Alnahdi et al, 2021 ). The results indicated that each of the five subscales had a unidimensional scale.…”
Section: Discussionsupporting
confidence: 92%
“…This is especially true for new topics, such as quality of life and the Arabic language. The BCFQOL scale is one of the most used scales with different samples from different cultures ( Park et al, 2003 ; Poston et al, 2003 ; Verdugo et al, 2005 ; Zuna et al, 2009 ; Balcells-Balcells et al, 2011 ; Meral et al, 2013 ; Parpa et al, 2016 ; Chiu et al, 2017 ; Schlebusch et al, 2017 ; Waschl et al, 2019 ; Balcells-Balcells et al, 2020 ; Kyzar et al, 2020 ). Psychometric properties were examined and showed good reliability and construct validity ( Hoffman et al, 2006 ), for example, in China, Hu et al (2012) findings supported the five-dimensional factor structure, and Chiu et al, 2017 results showed good fit indices for the five-factor model (first-order) with correlations between the five latent variables ranging from 0.70 to 0.93.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Content validity was assessed by presentation to experts [ 52 , 53 , 54 ]. For construct validity, exploratory factor [ 7 , 35 , 55 , 56 , 57 ] and confirmatory factor analyses [ 35 , 44 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] were used. Five factors have been identified for the BC-FQOoL scale in the CFA in several countries: Turkey [ 63 ], Singapore [ 60 ], Taiwan [ 62 ], Greece [ 57 ], Saudi Arabia [ 58 ], and Spain.…”
Section: Resultsmentioning
confidence: 99%
“…Each researcher should, therefore, establish a theoretical framework relevant to the specific objects of their study, whether it be the entire family, individual family members, or subsystems, to ensure consistency in the methodological design. Studies using mixed methodologies are also noteworthy [ 49 , 53 , 73 , 85 ]. Longitudinal studies have also been recommended for FQoL research [ 41 , 89 ].…”
Section: Discussionmentioning
confidence: 99%